STRUKTUR KEPRIBADIAN PROTAGONIS PADA CERPEN OREZ KARYA BUDI DARMA: KAJIAN PSIKOANALISIS FREUDIAN - Tiara Viona Veronica; Guntur Sekti Wijaya (Indonesian language and literature education program Majapahit Islamic University, 2024)
The purpose of this research was to describe the personality structure of the character ‘Saya’ in the short story Orez by Budi Darma using Freud’s psychoanalysis approach, especially about the three personality structures that focus on the id, ego, and superego of the character ‘Saya’. This research was a descriptive-qualitative research. The method of data collection was done with the note-taking technique. The analysis method used was by reducing data, presenting data, and drawing conclusions. The findings of this research showed that the ego structure is more dominant in controlling ‘Saya’ in his daily life, seen from the way ‘Saya’ faces internal conflicts between primitive desires and social norms. When the id emerges in the form of desire without considering the social impact, the ego acts as a mediator so that the desire is realised in a logical way. Meanwhile, the superego influences ‘Saya’s moral response to difficult situations. The three personality structures are very influential in shaping the behaviour and decisions of ‘Saya’.